FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PRE EKLAMSIA BERAT (PEB) DI RUMAH SAKIT UMUM PRINGSEWU TAHUN 2016 - Rohani, Siti; Wahyuni, Rini (Jurnal Kelitbangan Bappeda Pringsewu, 2018)
Pre-eclampsia is a complication that accounts for the maternal mortality rate. The incidence of pre-eclampsia in Indonesia 9.8% -25.5%. The incidence of pre-eclampsia in Lampung province by 27%. The incidence of pre-eclampsia may progress to eclampsia as well as increase the risk of maternal death, the fetus can lead to low birth weight, IUGR, prematurity, dysmaturity and IUFD or death of the fetus in the womb. The incidence of pre-eclampsia risk factors include: age, parity, race and ethnic factors, heredity (genetics), low education, low socio-economic, obesity, distended uterus berlebihandan history of maternal disease such as a history of hypertension, kidney disease, liver disease and history of diabetes mellitus (DM).This research generally aims to identify factors - factors related to the incidence of pre-eclampsia in hospitals Pringsewu 2016. The method used is an analytical method with case control design. Population is the case of mothers who have pre-eclampsia and the 36 mothers who do not control population is experiencing severe pre-eclampsia, amounting to 130 mothers. Samples numbered case and control samples 1 (24): 3 (72) maternal with quota sampling technique. How to measure with observation and questionnaire and checklist sheets measuring devices which are analyzed by univariate and bivariate percentage table with chi square analysis.The processing pre-eclampsia incidence proportion in the sample cases as much as 25% (24 mothers), 27.08% (26 mothers) with age at risk, 45, 83% (44 mothers) with parity risk, 4.17% (4 mothers ) with low education, 57.29% (55 mothers). Results of statistical tests the relationship of age with severe pre-eclampsia with p value: 0.034 and OR: 3.215, parity with pre-eclampsia with p value: 0,033 and OR: 3.143, education with pre eclampsia with p value: 0.49. Conclusion study maternal risk factors associated with the incidence of pre-eclampsia in hospitals Pringsewu 2016 is that there is a relationship between age, parity, and education with the incidence of severe pre-eclampsia, so it needs to be improved more intensive treatment efforts in women with pre-eclampsia, especially if there are signs of increased blood pressure, edema and protein urine.